2017
DOI: 10.3389/fpls.2017.02120
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Consistent QTLs of Wheat Spike-Related Traits under Nitrogen Treatment at Different Development Stages

Abstract: Spike-related traits such as spike length (Sl), fertile spikelet number (Fsn), sterile spikelet number (Ssn), grain number per spike (Gns), and thousand-kernel weight (Tkw) are important factors influencing wheat yield. However, reliably stable markers that can be used for molecular breeding in different environments have not yet been identified. In this study, a double haploid (DH) population was used for quantitative trait locus (QTL) mapping of five spike-related traits under four different nitrogen (N) sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…Based on the consensus map, the marker Excalibur_c5278_1075 (0.0 Mb) on 2D linked to the three spikelet numerical components was located at 2 cM from gpw4473, which was also reported to be associated with FSS (Yu et al, 2018). In addition, the marker CAP12_c1503_76 (35.6 Mb) also linked to TSS, FSS, and ESS in our study was very close to two regions reported to be associated with FSS and TSS by Deng et al (2017) and Yu et al (2018), respectively. In this region, Ellis et al (2005) also reported the marker GWM261 to be linked to Rht8 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Based on the consensus map, the marker Excalibur_c5278_1075 (0.0 Mb) on 2D linked to the three spikelet numerical components was located at 2 cM from gpw4473, which was also reported to be associated with FSS (Yu et al, 2018). In addition, the marker CAP12_c1503_76 (35.6 Mb) also linked to TSS, FSS, and ESS in our study was very close to two regions reported to be associated with FSS and TSS by Deng et al (2017) and Yu et al (2018), respectively. In this region, Ellis et al (2005) also reported the marker GWM261 to be linked to Rht8 .…”
Section: Discussionsupporting
confidence: 86%
“…In previous studies, stable genomic regions associated with TSS, FSS, and ESS were mainly detected on chromosomes 1A, 1B, 1D, 2A, 2B, 2D, 3A, 3B, 4B, 4D, 5A, 5D, 6A, 6B,7A, 7B, and 7D (Cui et al, 2012; Deng et al, 2017; Guo et al, 2017; Sun et al, 2017; Zhou et al, 2017; Liu et al, 2018; Yu et al, 2018). Here, we found MTAs linked to these traits on chromosomes 2A, 2D, and 7A.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the recent past, several genes controlling spike morphology have been investigated and described in temperate cereals (Gauley and Boden 2019; Koppolu and Schnurbusch 2019). From a plant breeder’s viewpoint, most spike morphological traits in wheat such as spike length and spikelet number behave as quantitative traits, and various QTL and association studies have recently been published (Deng et al 2017; Guo et al 2017; Liu et al 2018; Sakuma et al 2019; Würschum et al 2018; Zhai et al 2016). High associations and prediction abilities for total and fertile spikelet number as well as spike length and grain yield were also reported (Guo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…QSL.sicau-2AL was located around the position of 432.58 Mb at 2A, which was the same as QSl.sdau-2A[57]. QSL.sicau-2DS overlapped with QPht/SL.cau-2D.2[58], and the QSL.sicau-4AS was covered by QSl.sau-4A[59].…”
mentioning
confidence: 99%